2012
DOI: 10.1007/s10452-012-9421-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of zooplankton and phytoplankton in created shallow water habitats of the lower Missouri River: implications for native fish

Abstract: Shallow water habitat (SWH) is important for riverine fish and their invertebrate prey, yet the availability of SWH has declined in many systems due to human impacts. We evaluated the potential ecological benefits of restoring SWH by comparing zooplankton and phytoplankton from created backwaters (a floodplain feature connected to the river on the downstream end but disconnected at the upstream end) and chutes (a side channel of the river that diverts flow from the main channel through the chute and back into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Thus, high densities of rotifers were sampled during the first month of high water at all three floodplain sites. Mean rotifer densities sampled during the first month of floodplain sampling often exceeded those sampled from other lower Missouri River habitats including created backwater (<35 rotifers•L −1 ) and SWH chute sites (<10 rotifers•L −1 ) (Dzialowski et al, 2013) and the mainstem of the Missouri River near Dalbey (<100 rotifers•L −1 , USACE unpublished data); in contrast, mean densities from mainstem samples near Baltimore were as high as 290 rotifers• L −1 (USACE unpublished data) demonstrating that rotifer densities in the mainstem are capable of exceeding floodplain densities. Additionally, taxa richness, evenness and diversity peaked early at Baltimore and Dalbey (excluding trip 6 because of the lentic conditions discussed above).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, high densities of rotifers were sampled during the first month of high water at all three floodplain sites. Mean rotifer densities sampled during the first month of floodplain sampling often exceeded those sampled from other lower Missouri River habitats including created backwater (<35 rotifers•L −1 ) and SWH chute sites (<10 rotifers•L −1 ) (Dzialowski et al, 2013) and the mainstem of the Missouri River near Dalbey (<100 rotifers•L −1 , USACE unpublished data); in contrast, mean densities from mainstem samples near Baltimore were as high as 290 rotifers• L −1 (USACE unpublished data) demonstrating that rotifer densities in the mainstem are capable of exceeding floodplain densities. Additionally, taxa richness, evenness and diversity peaked early at Baltimore and Dalbey (excluding trip 6 because of the lentic conditions discussed above).…”
Section: Discussionmentioning
confidence: 87%
“…With relatively low water temperatures in European temperate lowland rivers, shallow habitats with a gentle bank slope warm up relatively fast in spring and summer. They often contain broad temperature gradients, which is beneficial for zooplankton production (Dzialowski et al, 2013; Górski et al., 2016) and for the metabolic processes in small fishes (Schiemer et al, 2002). The way in which both YOY fish and their prey respond to the interplay of river discharge, flow patterns and temperature, plays a major role in the population success of river fish (Humphries et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Shallow depths combined with slow‐moving water are prone to daily and seasonal temperature fluctuations that can influence the growth of age‐0 Scaphirhynchus spp. (Dzialowski et al ., ). Based on empirical SWH data from the Missouri River, we found that water temperature rarely exceeded 30 °C, a temperature that would not directly imperil sturgeon during a typical growing season.…”
Section: Discussionmentioning
confidence: 99%